Effects of ecological water diversion in coastal plain river network considering different control plans. Issue 1 (January 2021) - Wang, J M; Wu, J F; Fu, L; You, A J
Abstract: The water environment in coastal plain river network becomes serious due to its dense population and low flow rate, the ecological water diversion is widely accepted as an effective method to improve the water quality in coastal areas. As a typical coastal city in China, Pinghu city has suffered from the serious water quality problem for years especially in the downtown area. Therefore, the local water diversion project has been constructed since 2010 for the purpose of providing an efficient way to improve the river network water quality. However, a systematic research of the control plan of water diversion is still necessary. In this study, a numerical model is introduced to predict the improvement of river network water quality considering different control plans. The simulation results comparison among different water diversion control plans show than the pre-drainage plan obtains the best water quality in this coastal plain river network, and it becomes a good choice for the local government to further improve the regional water environment.